Efektivitas Pembelajaran Berbasis Portofolio pada Mata Kuliah Trigonometri - Radiatul Adawiah (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2019)
Effectiveness of portfolio learning on Trigonometry courses at the mathematics study program of STKIP Paris Barantai Kotabaru. The research subjects were 37 semester 2 students in the 2017/2018 academic year. This research was designed in the form of the Pretest-Posttest One Group. Data retrieval is done by using learning outcomes tests, portfolios, and observations. Data were analyzed using qualitative and quantitative analysis. The results achieved after applying portfolio-based learning are: (1) The pretest obtained an average score of mathematics learning outcomes of 6.5 students from the ideal score of 10 with a standard deviation of 1.5 while in Postest the average score of mathematics learning outcomes of students is 7.5 of the ideal score of 10 with a standard deviation of 1.4; (2) the average score of the portfolio results at pretest is 6.2 from the ideal score of 10 with a standard deviation of 1.1 while in the posttest the average score of the portfolio results is 7.0 from the ideal score of 10 with the standard deviation of 1.0; (3) there is a change in attitude that is better for each student by observing the indicators observed, namely the presence and activeness of students in asking questions to both the lecturer and friends, offering ideas / answering questions from lecturers and friends and helping friends in learning to improve over time to time; (4) there is progress in the level of students' ability to understand trigonometry material based on the monitoring of researchers when students complete the portfolio and the contents of the student portfolio. From the results of the analysis it can be concluded that portfolio-based learning can influence the results of second semester student mathematics learning, especially in trigonometry subjects. Keywords: Effectiveness, Learning, Portfolio, and Trigonometry